Arang satto chŏn Chosŏn sidae p'ant'aji nomaensŭ hwalgŭk - Kim, Sang-ho; Chŏng, Tae-yun; Chŏng, Yun-jŏng; I, Jun gi 1982-; Sin, Min a 1984-
""Arang and the Magistrate (Tale of Arang)" is the creative retelling of the classic horror folktale, "The Legend of Arang"--with a dash of comedy thrown into the mix. Against the backdrop of the Joseon Dynasty, the story between Arang, a wronged ghost, and Eunoh, the new magistrate who can see ghosts, is about fate, a truth greater than imagination, and the thin, and often blurred, line between life and death, the real and the surreal"--Hulu Website information